AN ANALYSIS OF MORAL VALUES OF THE RAINBOW TROOPS NOVEL BY ANDREA HIRATA - Lonasari Afandi (Journey: Journal of English Language and Pedagogy, 2018)
This research was conducted to describe the moral values based on the Novel Rainbow Troops. In conducting this research, the researcher used a descriptive qualitative method. The objective of the study are to find the moral values in Rainbow Troops novel. The method used in this study was document study. In this study, the researcher collected the data of the research dealing with the primary data source, using documentation. The findings of the moral values that were found in the novel are Individual Moral such as Discipline, Social Moral such as, Tolerance and Mutual Help, Religious Moral such as, Religious Education, Faith and Ethics, Cultural Moral and Educational Moral. The result of this research was expected to give additional information to reader and contribute to the development of literary study particularly among students who are interested in the literary study. Therefore, this study of reading novel or other books to make meaning, enjoy with learning process. It becomes one of alternative way to improve moral crisis in our life.